Java Enterprise in a nutshell - Farley, Jim (O'Reilly, 2005)
Nothing is as constant as change, and this is as true in enterprise computing as anywhere else. With the recent release of Java 2 Enterprise Edition 1.4, developers are being called on to add even greater, more complex levels of interconnectivity to their applications. To do this, Java developers today need a clear understanding of how to apply the new APIs, use the latest open source Java tools, and learn the capabilities and pitfalls in Java 2 Enterprise Edition 1.4 -- so they can plan a technology and implementation strategy for new enterprise projects. Fortunately, this is exactly what they get with the new Java Enterprise in a Nutshell , 3rd Edition. Because most integrated development environments (IDE) today include API lookup, we took out the main API sections from our previous edition to make room for new chapters, among others, on Ant, Cactus, Hibernate, Jakarta Struts, JUnit, security, XDoclet, and XML/JAXP. Revised and updated for the new 1.4 version of Sun Microsystems Java Enterprise Edition software, Java Enterprise in a Nutshell , 3rd Edition is a practical guide for enterprise Java developers.
Print version record
Keywords: Java (Computer program language); Application program interfaces (Computer software); Java (Langage de programmation); Interfaces de programmation d'applications; APIs (interfaces); Engineering & Applied Sciences; Computer Science; Certification